Diagnosis of Fraser syndrome missed out until the age of six months old in a low-resource setting: a case report - Aimé Mbonda; Francky Teddy Endomba; Ulrick S. Kanmounye; Jan René Nkeck; Joel Noutakdie Tochie (BMC, 2019)
Abstract Background Fraser syndrome is a rare genetic disorder that often presents with ocular, renal, genital and limb's congenital anomalies. The prognosis of this genetic disorder depends on the severity of the combination of congenital malformations, some of which may be fatal. The diagnosis of Fraser syndrome is based on established clinical criteria and genetic tests. The criteria enabling clinical diagnosis are visible dysmorphic features present at birth, hence, Fraser syndrome can easily diagnosed at birth, except when health professionals are inexperienced in clinical recognition. Herein, we report a case of Fraser syndrome missed out at birth and fortuitously diagnosed at the age of six months in a bid to raise clinicians' awareness, particularly in resource-limited settings. Case presentation We report a case of a six-month-old Cameroonian female infant, born at home and taken the following day to a primary healthcare facility for neonatal care. Her mother had no antenatal care until birth. She presented at our health center with respiratory distress and fever. She had a temperature of 38.8 °C and signs of left lung basal consolidation, suggestive of a left lower lober pneumonia, confirmed on chest x-ray. Other incidental clinical findings were several dysmorphic features like bilateral cryptophthalmos, nasal malformation, anal imperforation (with a perianal fistula), an external genital anomaly and syndactyly characteristic of Fraser syndrome associated with pneumonia. The patient responded well to intravenous antibiotics for the treatment of her pneumonia. Thereafter, she was referred to a pediatric surgeaon for surgical corrections of her bilateral cryptophthalmos, anal imperforation, external genital defect and syndactyly. Conclusion Here we presented a case of Fraser syndrome in a Cameroonian infant whose diagnosis was missed out at birth and fortuitously made at six months of age. In view of the serious and potentially fatal complications of this genetic disorder, we draw clinicians' attention, especially obstetricians, midwives and pediatricians for a high index of clinical suspicion geared at a timely diagnosis and management. Also, for a timely diagnosis, health education on regular antenatal and postnatal follow ups of  the mother-infant couple respectively, cannot be overemphasized.